Analisis Pengalaman Penyeduh Pemula dalam Mengenal Profil Sensori Kopi Aceh Gayo ‘Drama’ pada Kegiatan Komunitas Koffie Rakjat Semarang - Natalia Sari Pujiastuti; Yasirly Maulayya Anjani Yonda; Cherryna Putri Khoirunnisa; Aditiya Panji Satrio; Rizal Aditiya Saputra; Rahmat Basuki; Akbar Berliansyah Putra Marhar (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The “Beginner Brewer” community activity organized by Koffie Rakjat Semarang stands out as an informal learning space for individuals new to coffee brewing techniques, but so far there has been little scientific study regarding its impact on participants’ sensory experiences. This study aims to analyze how beginners understand and evaluate the flavor profile of Aceh Gayo single-origin coffee “Drama” through practical brewing sessions. The research method used a qualitative descriptive approach with data sources consisting of activity documentation, observations of popular articles, and direct quotations from participants’ experiences. The results showed that mentoring with simple techniques such as the V60 (1:15) and French Press (1:12) contributed to participants’ increased understanding of the fruity character and flavor complexity of “Drama,” which has flavor notes of passion fruit, pineapple, strawberry jam, rum, and palm sugar. Participants also reported that the inclusive learning environment made the brewing process easy and enjoyable, and encouraged continued interest in specialty coffee. In conclusion, this community activity is effective as an initial educational tool that shapes flavor perception and increases the confidence of beginner brewers in understanding specialty coffee.